Избранные сочинения - Жуковский Василий Андреевич (Библиотека классики, 1982)
Экземпляры: ф. 4 (20141111) / Инвентарный номер: 101797 / Цена: 15.00 / Авт.знак: Ж 86 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1